Addressing the Life Cycle of Sewers in Contrasting Cities through an Eco‐Efficiency Approach. (5th September 2017) - Petit‐Boix, Anna; Arnal, Carla; Marín, Desirée; Josa, Alejandro; Gabarrell, Xavier; Rieradevall, Joan
Summary: Evaluating the sustainability of the urban water cycle is not straightforward, although a variety of methods have been proposed. Given the lack of integrated data about sewers, we applied the eco‐efficiency approach to two case studies located in Spain with contrasting climate, population, and urban and sewer configurations. Our goal was to determine critical variables and life cycle stages and provide results for decision making. We used life cycle assessment and life cycle costing to evaluate their environmental and economic impacts. Results showed that both cities have a similar profile, albeit their contrasting features, that is, operation and maintenance, was the main environmental issue (50% to 70% of the impacts) and pipe installation registered the greatest economic capital expenditure (70% to 75%) due to labor. The location of the wastewater treatment plant (WWTP) is an essential factor in our analysis mainly due to the topography effects (e.g., the annual pump energy was 13 times greater in Calafell). Using the eco‐efficiency portfolio, we observed that sewers might be less eco‐efficient than WWTPs and that we need to envision their design in the context of an integrated WWTP‐sewer management to improve sewer performance. In terms of methodological approach, the bidimensional nature of eco‐efficiency enables the benchmarking of product systems and might be more easily interpreted by the general public. However, there are still some constraints that should be addressed to improve communication, such as the selection of indicators discussed in the article.